IMMUNOBIOLOGY OF ACUTE GRAFT-VERSUS-HOST DISEASE - G. A. Efimov; A. S. Vdovin; A. A. Grigoryev; S. Yu. Filkin; N. A. Bykova; V. G. Savchenko (Медицинская иммунология, 2016)
Transplantation of allogeneic hematopoietic stem cells is the only curative option for a number of diseases of hematopoietic system. It is intended to replace the hematopoietic system of the recipient withthe donor’s. However, when mature T cells contained in the graft enter the recipient organism, it may lead to a severe post-transplant complication, the “graft versus host” disease (GVHD). It occurs due to the fact that the donor immune system contains T cell clones specific to recipient alloantigens. These cell clones are activated upon encountering their antigens, thus causing systemic damage to healthy tissues. Development of the alloreactive clones is caused by genetic differences between donor and recipient. The most importantfactors determining successful transplantation concern the compatibility for the genes coding for Major Histocompatibility Complex (MHC), that are expressed in all nucleated cells and are responsible for antigen presentation to the immune cells. Currently established extensive donor banks allow for majority of patients to choose a compatible donor. However, this does not provide complete prevention of the GVHD development, because in addition to the MHC genes the donor and recipient may differ in so-called minor histocompatibility antigens. Minor antigens may be caused by genetic polymorphisms in all of the genome coding regions. Pre-transplantation conditioning of the patient, which is necessary for engraftment represent an additional factor contributing to the GVHDdevelopment, since as its side effect it leads to formation of a pro-inflammatory environment in the organism of recipient. Severe GVHD develops in approximately 40% of MHC-matched patients, while in cases of partial compatibility this proportion is even higher. GVHD causes mortality comparable to other causes of posttransplantdeath, such as viral infections or relapse of underlying disease. Thus, the development of severe GVHD is a significant limitation for clinical applications of stem cell transplantation. Severe immunesuppression or depletion of mature donor T cells from the transplant leads to increased probability of relapse and weakens anti-infectious immunity. Hence, further search for alternative, more specific ways to prevent GVHD is required. This review will focus on the mechanisms of alloreactive T lymphocyte clone development and key pathogenetic stages of acute “graft versus host” disease.